Once Upon a Camel - Appelt, Kathi, 1954-; Rohmann, Eric (New York : Atheneum Books for Young Readers, 2021)
In 1910, Zada the camel treks across the West Texas desert to save two baby kestrels from an approaching haboob, a mountain-sized storm. sharing adventures from her youth in Turkey to keep them calm.
Keywords: Camels -- Juvenile fiction; Kestrels -- Juvenile fiction; Animals -- Juvenile fiction -- Infancy; Dust storms -- Juvenile fiction; Storytelling -- Juvenile fiction; Camels -- Fiction; Kestrels -- Fiction; Animals -- Fiction -- Infancy; Dust storms -- Fiction; Storytelling -- Fiction; Texas -- Juvenile fiction -- History -- 1865-1950; Turkey -- Juvenile fiction -- History -- Abdul Mejid, 1839-1861; Texas -- Fiction -- History -- 1865-1950; Turkey -- Fiction -- History -- Abdul Mejid, 1839-1861